Mitochondrial Fragmentation Is an Important Cellular Event Induced by Ruthenium(II) Polypyridyl Complexes in Osteosarcoma Cells. Issue 4 (8th January 2014) - Du, Yanxin; Fu, Xiaoyan; Li, Hong; Chen, Bolai; Guo, Yuhai; Su, Guoyi; Zhang, Hu; Ning, Feipeng; Lin, Yongpeng; Mei, Wenjie; Chen, Tianfeng
Abstract A series of ruthenium(II) polypyridyl complexes were synthesized and evaluated for their in vitro anticancer activities. The results showed that ruthenium polypyridyl complexes, especially [Ru(bpy)2(p‐tFPIP)]2+ (2 a; bpy=bipyridine, tFPIP=2‐(2‐trifluoromethane phenyl)imidazole[4, 5‐f][1, 10]phenanthroline), exhibited novel anticancer activity against human cancer cell lines, but with less toxicity to a human normal cell line. The results of flow cytometry and caspase activities analysis indicated that the 2 a‐induced growth inhibition against MG‐63 osteosarcoma cells was mainly caused by mitochondria‐mediated apoptosis. DNA fragmentation and nuclear condensation as detected by TUNEL–DAPI co‐staining further confirmed 2 a‐induced apoptotic cell death. Further, fluorescence imaging revealed that ruthenium(II) polypyridyl complexes could target mitochondria to induce mitochondrial fragmentation, accompanied by depletion of mitochondrial membrane potential. Taken together, these findings suggest a potential application of theses ruthenium(II) complexes in the treatment of cancers.